2014
DOI: 10.1088/1054-660x/24/8/085101
|View full text |Cite
|
Sign up to set email alerts
|

A switchable and wavelength-spacing tunable single-frequency and single-polarization dual-wavelength erbium-doped fiber laser based on a compound-cavity structure

Abstract: A switchable and wavelength-spacing tunable single-frequency and single-polarization dual-wavelength erbium-doped fiber laser is proposed and demonstrated experimentally. The fiber laser is composed of a main linear cavity and two subring cavities. In dual-wavelength operation, the wavelength spacing can be tuned from 0.430 nm to 4.487 nm, showing that the fiber laser can be used for photonic generation of a microwave signal with a tunable frequency range from 54 GHz to 563 GHz; in single-wavelength operation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In 2014, Feng et al reported a dual-wavelength tunable EDFL based on narrow-band FBG (NB-FBG), which can switch single and dual wavelength. Moreover, by controlling the stress applied on the NB-FBG, an interval of tunable dual-wavelength from 0.430-4.847 nm is achieved [17]. In 2018, Ibarra-Escamilla et al reported a tunable dual-wavelength operation of an all-fiber thuliumdoped fiber laser based on tunable FBG, where an interval of tunable dual wavelength from 0.54-9.00 nm is obtained [18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Feng et al reported a dual-wavelength tunable EDFL based on narrow-band FBG (NB-FBG), which can switch single and dual wavelength. Moreover, by controlling the stress applied on the NB-FBG, an interval of tunable dual-wavelength from 0.430-4.847 nm is achieved [17]. In 2018, Ibarra-Escamilla et al reported a tunable dual-wavelength operation of an all-fiber thuliumdoped fiber laser based on tunable FBG, where an interval of tunable dual wavelength from 0.54-9.00 nm is obtained [18].…”
Section: Introductionmentioning
confidence: 99%
“…Dual-wavelength erbium-doped fiber lasers (EDFLs) have attracted much interest due to their various applications in wavelength division multiplexing (WDM) systems, optical sensing, optical testing, laser radars and generation of terahertz radiation [1][2][3][4][5]. Up to now, dual-wavelength EDFLs with tunable wavelength spacing have been constructed using various optical devices, such as fiber Bragg gratings (FBGs) [6][7][8][9], polymer waveguide Bragg gratings [10,11], volume Bragg gratings [12], and Mach-Zehnder interferometers [13,14]. Jeon et al proposed a tunable dual-wavelength EDFL, in which the spectral spacing can be tuned from 3.2 to 9.6 nm by using two FBGs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, an ultra-narrow band-pass filter must be used to eliminate multi-longitudinal-mode (MLM) oscillation and mode hopping. 15 To achieve SLM operation, various mode suppression techniques have been proposed, such as phase-shifted fiber Bragg grating (FBG) with ultra-narrow bandwidth, 16 a high finesse FBG based Fabry-Perot (FP) etalon, 17 a compound ring, 17,18 passive multiple ring cavities, 18,19 a saturable absorber (SA) inducing spatial-hole burning as a dynamic narrow bandwidth filter 20 and a FBG as selfinjection feedback. 21,22 Combining these controlling technologies with FBG, intra-cavity FP filter or FBG based FP etalon, 17 both wavelength tunable and SLM operation have been realized simultaneously.…”
Section: Introductionmentioning
confidence: 99%